PENGARUH KOMPENSASI DAN KINERJA KARYAWAN TERHADAP DISIPLIN KERJA PADA KARYAWAN PT.TELKOM PALOPO - Revi; Sukri; Riyanti (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to examine the impact of compensation and employee performance on work discipline levels at PT Telkom in Palopo City. The approach used is a quantitative method with a causal design, where data is collected through the distribution of questionnaires. The research population includes all employees of PT Telkom Palopo, and the sampling method used is a saturated sampling technique (census), where all 40 members of the population are included as samples in this study. The collected data is then analyzed using SPSS version 26. The findings of this study indicate that both compensation and employee performance have a positive influence on employee work discipline at PT Telkom Palopo.